Association of BMI and WC for insulin resistance and type 2 diabetes among Brazilian adolescents - Cesar Pirajá Bandeira; Beatriz D. Schaan; Felipe Vogt Cureau (Jornal de Pediatria)
Objective: To investigate how body mass index (BMI) and waist circumference (WC) may be associated with insulin resistance and type 2 diabetes (T2DM) in Brazilian adolescents. Methods: Cross-sectional study using data from the Brazilian Study of Cardiovascular Risks in Adolescents (ERICA) including adolescents aged 12–17 years. The relationship between adiposity and T2DM was investigated using ordinal logistic regression models. To study the association between adiposity categories and the occurrence of insulin resistance, linear regression models were used. Results: The prevalence of T2DM for the same BMI category did not increase with the presence of high WC. Regarding insulin resistance, for the same BMI categories, having a high WC resulted in a higher prevalence of insulin resistance (HOMA-IR). The only groups significantly associated with prediabetes and T2DM were those with obesity by BMI with elevated WC (POR 1.68, 95 % CI 1.45; 1.94) and obesity with normal WC (POR 1.58, 95 % CI 1.01; 2.46). Similar findings were observed concerning insulin resistance, where the increased WC had its greatest effect when associated with obesity by BMI (β Coefficient 2.20, 95 % CI 1.89; 2.50). Conclusion: The combination of BMI and WC is better for assessing adolescents at risk of developing T2DM.